Answer:
2 Right Angled Triangles
Step-by-step explanation:
Find the value of n 5^10 ÷ 5^8=(1/5)^n
Answer:
5^10 / 5^8 = 5^2 = 25 so the equation becomes 25 = (1/5) ^ n. This means that n = -2.
Answer:
[tex]n=-2[/tex]
Step-by-step explanation:
[tex]\frac{5^{10}}{5^8}=(\frac{1}{5})^n[/tex]
Use the law of exponents.
[tex]5^{10-8}=\left(\frac{1}{5}\right)^n[/tex]
1/5 can be written with a base of 5.
[tex]5^{10-8}=\left(5^{-1}\right)^n[/tex]
Cancel the base 5 on both sides.
[tex]10-8=-1\times \:n[/tex]
[tex]2=-n[/tex]
Multiply both sides with -1.
[tex]n=-2[/tex]
CAN ANYONE HELP ASAP!!!!
Answer:
C and D
Step-by-step explanation:
since sqrt(4) = 2, we can replace all of the sqrt(4) in D to 2
Once we do that, it becomes
2 1
1 2
2 1
or C
Please answer correctly !!!!!!!! Will mark brainliest !!!!!!!!!!!!!
Answer:
The discriminant is 0
That means there is one real zero
Step-by-step explanation:
3x^2 + 24x + 48
This in the form
ax^2 +bx+c
a=3 b=24 c = 48
The discriminant is
b^2 - 4ac
24^2 - 4(3)(48)
576-576
0
The discriminant is zero
That means there is one real zero
Lliana started to evaluate the function f(x)=2x^2-3x+7 for the input value 2. What is the value of the function when x=2?
Answer:it is 9 because you subtract 6 from the 8 and then you add 2 and 7 to get 9
Step-by-step explanation:
Which statement best explains why this expression is equal to 9.4? A)Any expression multiplied by 0 equals 0. B)Any number divided by its opposite equals 0. C)The fraction is equal to −9.4. Any number added to its opposite results in the number itself. D)The expression does not have a value of 9.4.
Answer: A.
Step-by-step explanation:
yeet
Answer:
A.
Step-by-step explanation:
Because if you multiply out the top of the fraction to simplify it, it will equal zero. And zero divided by any number is equal to zero because no number fits into zero. So A. would be the best answer since you are multiplying an expression by zero on the top, and you can't get any number other then zero for the answer of the fraction. And 0 + 9.4 = 9.4.
2/5 y + 1/5 x -0.2y - 6 + (-2)
Answer:
[tex]0.2y+0.2x-8[/tex]
Step-by-step explanation:
[tex]\frac{2}{5}y+\frac{1}{5}x-0.2y-6+\left(-2\right)[/tex]
[tex]=\frac{2}{5}y+\frac{1}{5}x-0.2y-6-2[/tex]
[tex]=\frac{2}{5}y-0.2y+\frac{1}{5}x-6-2[/tex]
[tex]\frac{2}{5}y-0.2y[/tex]
[tex]=y\left(\frac{2}{5}-0.2\right)[/tex]
[tex]\frac{2}{5}-0.2=0.2[/tex]
[tex]=0.2y[/tex]
[tex]=0.2y+\frac{1}{5}x-6-2[/tex]
[tex]\frac{1}{5}x[/tex]
[tex]=\frac{1\cdot \:x}{5}[/tex]
[tex]=\frac{x}{5}[/tex]
[tex]=0.2y+\frac{x}{5}-6-2[/tex]
[tex]=0.2y+0.2x-8[/tex]
Which of these choices are quadratic equations? Check all that apply.
A. 2x – 1 = 0
B. 2x2 - 1 = 0
C. 2x2 - 1
D. 3x2 + 5x - 1 = 0
E. x - x² +5=0
F. - 4x2 + x = 0
Answer:
Quadratic Equations ⇒ D, E, F
Step-by-step explanation:
Let us say that each of these equations can only be defined as a quadratic equation if it can be factored / solved through completing the square / application of quadratic formula as solve for the value of x;
[tex]A. 2x - 1 = 0, Add + 1 to either side,\\2x = 1, Divide sides by 2,\\x = 1 / 2 ; Not Quadratic Equation[/tex]
[tex]B. 2x^2 - 1 = 0, Add + 1 to either side,\\2x^2 = 1, Divide sides by 2,\\x^2 = 2, Take | | of x, \sqrt{x} - either side \\\| x | = \sqrt{1 / 2},\\x = \sqrt{1 / 2} = - \sqrt{1 / 2} ; NotQuadraticEquation[/tex]
[tex]C. 2x^2 - 1, NotInForm - ax^2 + bx + x = 0 ; NotQuadraticEquation[/tex]
[tex]D. 3x^2 + 5x - 1 = 0, Add 1 to either side,\\3x^2 + 5x = 1, Divide sides by 3,\\x^2 + 5x / 3 = 1 / 3, Solve for a,\\2ax = 5 / 3x, Divide sides by 2x,\\a = 5 / 6, Add a^2 - ( 5 / 6 )^2 to either side,\\x^2 + ( 5x / 3 )^2 + ( 5 / 6 )^2 = 1 / 3 + ( 5 / 6 )^2, simplify,\\( x + 5 / 6 )^2 = 37 / 36, solve for x,\\x = ( \sqrt{37} - 5 ) / 6 = ( - \sqrt{37} - 5 ) / 6 ; QuadraticEquation[/tex]
[tex]E. x - x^2 + 5 = 0, Similar Form ; QuadraticEquation\\[/tex]
[tex]F. - 4x^2 + x = 0, Factor the Expression,\\- x * ( 4x - 1 ) = 0, Apply Zero Product Property,\\x = 0, and, 4x - 1 = 0,\\x = 0 = 1 / 4 ; QuadraticEquation[/tex]
The quadratic equations are:
2x² - 1 = 0
2x² - 1
3x² + 5x - 1 = 0
x - x² +5 = 0
-4x² + x = 0
Options B, C, D, E and F are the correct answer.
What is a polynomial?Polynomial is an equation written as the sum of terms of the form kx^n.
where k and n are positive integers.
We have,
A polynomial with degree 2 is called a quadratic equation.
A.
2x – 1 = 0
This is not a degree 2 equation.
B.
2x² - 1 = 0
This has degree 2.
C.
2x² - 1
This has degree 2.
D.
3x² + 5x - 1 = 0
This has degree 2.
E.
x - x² +5 = 0
-x² + x + 5 = 0
This has degree 2.
F.
- 4x² + x = 0
This has degree 2.
Thus,
B, C, D, E, and F are quadratic equations.
Learn more about polynomials here:
https://brainly.com/question/2284746
#SPJ2
Question 1 (1 point)
What is the solution set to the equation x+1=2
Question 2 (1 point)
Consider the equation x +1 = 2.
Rewrite the equation by multiplying both sides by x +1
DO NOT USE A MULTIPLICATION SYMBOL
Question 3 (1 point)
Solve the equation for
5(2x - 4) - 11 = 4 + 3x
please answer all if possible. Thanks
Answer:
See below
Step-by-step explanation:
1) x=2-1
x=1
2) (x+1)(x+1)=2(x+1)
3) 10x-20 -11 = 4+3x
10x-3x=20+11+4
7x=35
x=5
plz help with slope question fast
Answer:
The Answer is D. because -4 passes trough the x intercept and -2 passes through the y
Step-by-step explanation:
Answer:
The answers are:
x-intercept = -4
y-intercept = -2
Step-by-step explanation:
According to the following to graph, you need to find the x-intercept and the y-intercept. The x-intercept, is when a line crosses the x-axis of the graph, and the y-intercept, is when a line crosses the y-axis of the graph.
Finding the x-intercept and the y-intercept:
x-intercept = -4
y-intercept = -2
determine the kinetic energy of 745-kg roller coaster car that is moving with a speed of 14.9 m/s
Answer:
≈82698.73 kg m²/s
Step-by-step explanation:
K.E.=1/2mv²=1/2×745×14.9²=82698.725 kg m²/s
What is the solutions for x in the equation -2x+14+10x=34
Answer:
x=2.5
Step-by-step explanation:
Put the like terms together, like so:
10x-2x=34-14
The result is this:
8x=20
Simplify to get:
x=2.5
Answer:
x= 2 1/2 or x=2.5
Please answer correctly !!!!!!!! Will mark brainliest !!!!!!!!!!
Answer:
x^2+6x+9
Step-by-step explanation:
x^2 +6x
Take the coefficient of x
6
Divide by 2
6/2 = 3
Square it
3^2 = 9
Add 9 to each side
x^2+6x+9
Please answer correctly !!!!!! Will mark brianliest !!!!!!!!!!!
Answer: 2
Step-by-step explanation:
Which is a simplified form of the expression 2(2j + 3) – 3j? A. -j + 3 B. 2j + 3 C. j + 6 D. -j + 6
Answer:
C. j + 6
Step-by-step explanation:
2(2j + 3) - 3j
multiply each term in the parentheses by 2
2 x 2j + 2 x 3
calculate the product
4j + 6 -3j
collect like terms by subtracting their coefficients
(4 - 3)j
then subtract the numbers
1j
when the term has a coefficient of 1, it doesn't have to be written
j
then plug in the other number and that's your answer
j + 6
Answer:
The answer is C).Step-by-step explanation:
C. j + 6
Hope this helps!! :)
Evaluate the expression for p = 4.
p^2=
4^2 = 4 * 4.
4 * 4 = 16.
Therefore, p ^2 = 16.
Answer:
16
Step-by-step explanation:
i showed the work in the picture above
plslslslsl help ASAP you win win brainlist
Answer:
78 dollars
Step-by-step explanation:
Take the prices and multiply by the percent commission
778 * 10 %
Change to decimal form
778 * .10
77.80
Round to the nearest dollar
78
Answer:77.80
Step-by-step explanation:
For which x is f(x)?=-3
Answer:
[tex]-7[/tex]
Step-by-step explanation:
[tex]f(-3)=-7[/tex]
Emma spent $21.23 on two thousand bagels and a gallon of iced tea the price of the gallon of iced tea with $5.25 the following equation can be used to find d the price of the each dozen of bagels
Answer:
$21.23 - $5.25 = d
Step-by-step explanation:
Please answer correctly !!!!!!! Will mark brainliest !!!!!!!!!!!
Answer:
et's solve your equation step-by-step.
(x+3)2−1=35
Step 1: Simplify both sides of the equation.
x2+6x+8=35
Step 2: Subtract 35 from both sides.
x2+6x+8−35=35−35
x2+6x−27=0
Step 3: Factor left side of equation.
(x−3)(x+9)=0
Step 4: Set factors equal to 0.
x−3=0 or x+9=0
x=3 or x=−9
Answer:
x=3 or x=−9
Answer:
Add 1 to each side
Take the square root of each side
Subtract 3 from each side
Step-by-step explanation:
(x+3)^2 -1 = 35
Add 1 to each side
(x+3)^2 -1+1 = 35+1
(x+3)^2 = 36
Take the square root of each side
sqrt ((x+3)^2) =±sqrt (36)
x+3 = ±6
Subtract 3 from each side
x+3-3 = -3±6
x = -3±6
x = -3+6 x = -3-6
x = 3 x = -9
Emma needs 40 pieces of string to wrap presents. Each piece of string is 7.5 inches. If the ribbon is only available in feet, how many feet of ribbon does Emma need?
Answer:
2635*'fhhdgjvsvaksgwksygwi at gwjsksgeieh egg ejei
Find the value of x in the triangle shown below
Answer:
28°
Step-by-step explanation:
every Triangle equals to 180°
85+67=152
180-152=28
????????????????????
Answer:
A) DEBBIE: 1p+4t=29
B) JOEY: 5p+2t=28
Step-by-step explanation:
Verticle angles must have ?
Answer: Verticals angles are when 2 line intersect at a point forms 2 pairs of angles. The pairs will be opposite of each other.
The picture I have attached should give a good representation of what I mean.
The A angles are the same and the B angles are the same in the picture.
A pentagon train is made by attaching regular pentagons with 1" sides so that each pentagon, except the two on the ends, is attached to exactly two other pentagons along sides, as shown. How many inches are in the perimeter of a pentagon train made from 85 pentagons?
Answer:
There are 341 inches from the perimeter of a pentagon train made from 85 pentagons
Step-by-step explanation:
A pentagon is a polygon with five sides. A regular pentagon have all the five sides equal in length and also all the five interior angles equal.
The perimeter of a pentagon = 5l
Nof for a pentagon train attached to 1 pentagon by its sides;
The perimeter = (5 × 1 - (1-1))
Perimeter = 5
For pentagon train attached to two pentagon
Perimeter = ( 5×2 - (2-1))
Perimeter = (10 1)
Perimeter = 9
For pentagon train with n pentagon
Perimeter = ( 5× n -(n-1))
Perimeter = 5n - n+1
Perimeter = 4n + 1
∴ For pentagon train attached to 85 pentagon; where n=85
Perimeter = 4 n + 1
Perimeter = (4 × 85)+1
Perimeter = 340+1
Perimeter = 341 inches
There are 341 inches from the perimeter of a pentagon train made from 85 pentagons
The dimensions of a box are x, 2x, and 3x. Each dimension is increased by 3. Calculate the volume of the box.
Answer:
The volume of the box would be 6x³+33x²+54x+27.
Step-by-step explanation:
The new dimensions of the box would be (x+3), (2x+3), and (3x+3). Since the volume of a rectangular prism are calculated by multiplying the length, width, and depth, we can just multiply all three of these dimensions together to come up with the answer.
Using foil on the first two terms originally you get (x+3)×(2x+3)= 2x²+3x+6x+9 which can be simplified to 2x²+9x+9.
Then you multiply this equation by (3x+3). (2x²+9x+9)×(3x+3)= 6x³+6x²+27x²+27x+27x+27 which can be simplified to 6x³+33x²+54x+27.
Answer:
6x³+33x²+54x+27
Step-by-step explanation:
dimensions are now:
x+3, 2x+3, 3x+3
Volume
V=lwhV= (x+3)(2x+3)(3x+3)= 3(x+1)(x+3)(2x+3)= 3( x² + 4x+3)(2x+3)= 3(2x³+11x²+18x+9)=6x³+33x²+54x+27Which of the following describes the translation of the graph of y=x? to obtain the graph of y=-x2+3?
reflect over the x-axis and shift right 3
o reflect over the x-axts and shift up 3
reflect over the y-axis and shift down 3
Answer:
Reflect over the x-axis and shift up 3.
Answer:
Reflect over the x-axis and shift up 3
Step-by-step explanation:
Which expression can be used to find 38 percent of 22?
Answer:
[tex]0.38 \times 22[/tex]
Step-by-step explanation:
The correct expression used to find 38 percent of 22 is
[tex]0.38 \times 22[/tex]
A circular rug has a radius of 10 feet. What is the area of the rug? Use 3.14 for π.
Enter your answer
Answer:
A=314 feet
Step-by-step explanation:
[tex]A=\pi r^{2}[/tex]
[tex]A=3.14*10^{2}[/tex]
[tex]A=3.14*100[/tex]
[tex]A=314 feet[/tex]
if p(x) = x^99 + 99 , then find p(1)
Answer:
p(1)=100
Step-by-step explanation:
p(1) just means "substitute the value (1) in for (x) in the equation"
So,
[tex]1^{99}[/tex]+99= 100
(1 to any power is always equal to 1, including 0)
what does 9n-2<7+20 equal?
Answer:
[tex]n<\frac{29}{9}\\n<3.222222.....\\[/tex]
n ≈ 3
Step-by-step explanation:
9n-2<7+20
[tex]9n-2<27 \leftarrow \text {Combine Like Terms}\\9n-2+2<27+2 \leftarrow \text {Addition Property of Equality}\\9n<29\\\frac{9n<29}{9} \leftarrow \text {Divsion Property of Equality}\\\boxed{n<\frac{29}{9}}[/tex]